FUGITIVE EMISSONS FROM ENERGY SECTOR IN THE REPUBLIC OF MOLDOVA - Bicova E.V; Tsaranu M.H.; Burtsev S.V. (Problems of the Regional Energetics)
The paper contains the results of the process of inventorying the fugitive emissions from energy sector of the Republic of Moldova. It is described the applied methodology, activity data used, there were analyzed the trends of methane emissions during the 1990-2005 period, as well as additional information is presented for evaluating CO2 and N2O fugitive emissions from natural gas transmission and distribution in the Republic of Moldova.